Pilot trial of inosine to elevate urate levels in amyotrophic lateral sclerosis. Issue 12 (22nd October 2018) - Nicholson, Katharine; Chan, James; Macklin, Eric A.; Levine‐Weinberg, Mark; Breen, Christopher; Bakshi, Rachit; Grasso, Daniela L.; Wills, Anne‐Marie; Jahandideh, Samad; Taylor, Albert A.; Beaulieu, Danielle; Ennist, David L.; et al.
Abstract: Objective: To test the safety, tolerability, and urate‐elevating capability of the urate precursor inosine taken orally or by feeding tube in people with amyotrophic lateral sclerosis (ALS). Methods: This was a pilot, open‐label trial in 25 participants with ALS. Treatment duration was 12 weeks. The dose of inosine was titrated at pre‐specified time points to elevate serum urate levels to 7–8 mg/dL. Primary outcomes were safety (as assessed by the occurrence of adverse events [AEs]) and tolerability (defined as the ability to complete the 12‐week study on study drug). Secondary outcomes included biomarkers of oxidative stress and damage. As an exploratory analysis, observed outcomes were compared with a virtual control arm built using prediction algorithms to estimate ALSFRS‐R scores. Results: Twenty‐four out of 25 participants (96%) completed 12 weeks of study drug treatment. One participant was unable to comply with study visits and was lost to follow‐up. Serum urate rose to target levels in 6 weeks. No serious AEs attributed to study drug and no AEs of special concern, such as urolithiasis and gout, occurred. Selected biomarkers of oxidative stress and damage had significant changes during the study period. Observed changes in ALSFRS‐R did not differ from baseline predictions. Interpretation: Inosine appeared safe, well tolerated, and effective in raising serum urate levels in people with ALS. These findings, together with epidemiological observations and preclinical data supporting a neuroprotective role of urate in ALS models, provide the rationale for larger clinical trials testing inosine as a potential disease‐modifying therapy for ALS.